Modal Interferometer Using Three-Core Fiber for Simultaneous Measurement Strain and Temperature - Tao Geng; Jiang He; WenLei Yang; XuDong Chen; MaoWei An; CuiTing Sun; XiRen Jin; Libo Yuan (IEEE Photonics Journal)
A structure made of tapered three-core fiber and CO2 laser notch long-period fiber grating is proposed in this paper. By adjusting the taper waist diameter of a three-core fiber, this structure is made suitable for simultaneous strain and temperature measurements. The effectiveness of the proposed structure in realizing simultaneous measurement sensitivity is verified by measuring the sensitivities of the two peaks at the variation of the wavelength and the depth difference. Experimental results indicate that the wavelength sensitivities of the two peaks are $-2.96\ \text{nm m}ε^{-1}$ , 42.9 pm °C−1 and $-1.52\ \text{nm m}ε^{-1}$ , 47.4 pm °C−1 for strain and temperature, respectively, and the depth sensitivities of two peaks can reach 2.5 dB $\text{m}ε^{-1}$ , 0.007 dB °C−1 and $-2.8\ \text{dB m}ε^{-1}$ , −0.013 dB°C−1. It can therefore be concluded that the proposed structure can be realized by adjusting the taper waist diameter of a three-core fiber for simultaneous strain and temperature measurements.